2013
DOI: 10.1016/j.toxlet.2013.08.026
|View full text |Cite
|
Sign up to set email alerts
|

The critical importance of defined media conditions in Daphnia magna nanotoxicity studies

Abstract: Due to the widespread use of silver nanoparticles (AgNPs), the likelihood of them entering the environment has increased and they are known to be potentially toxic. Currently, there is little information on the dynamic changes of AgNPs in ecotoxicity exposure media and how this may affect toxicity. Here, the colloidal stability of three different sizes of citrate-stabilized AgNPs was assessed in standard strength OECD ISO exposure media, and in 2-fold (media2) and 10-fold (media10) dilutions by transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…Romer et al 26 Unlabeled NPs were synthesized primarily to allow the synthesis method to be validated on the relatively inexpensive unlabeled Ag starting material.…”
Section: Nanoparticle Synthesismentioning
confidence: 99%
“…Romer et al 26 Unlabeled NPs were synthesized primarily to allow the synthesis method to be validated on the relatively inexpensive unlabeled Ag starting material.…”
Section: Nanoparticle Synthesismentioning
confidence: 99%
“…While it has been shown that media composition can influence particle stability Römer et al 2013), the aggregation behavior of 1 mg/L AgNPs was assessed at 0, 1, 4, 24, and 48 h to correspond to the duration of the toxicity exposure study (Fig. 1b).…”
Section: Characterization and Stability Evaluation Of Agnpsmentioning
confidence: 99%
“…1b) probably due to the settling of aggregates in SCM. The rate of aggregation is affected by both the collapse of the diffuse layer of counter ions around the particle and the frequency of particle-toparticle interactions, as a consequence of the higher concentration of AgNPs (Römer et al 2013). Therefore, it is possible that the AgNPs used in the bioassays were less aggregated than suggested by results presented in Table 1 and Fig.…”
Section: Characterization and Stability Evaluation Of Agnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Publications dealing with this aspect (see also SI Table S4) underline the relevance of ionic strength for aggregation of TiO 2 NP and Ag NP (Dabrunz et al, 2011;Romer et al, 2013;Romer et al, 2011;Tejamaya et al, 2012;Zhao and Wang, 2012). Moreover, charge-stabilized EINP dispersions are less stable than EINP coated with polyethylene glycol or PVP (Tejamaya et al, 2012).…”
Section: Aging Of Einp In Artificial Test Mediamentioning
confidence: 99%